Google Sites Learning Media to Improve Critical Thinking Skills in Elementary School Students - Suhendro Purwanto; Eges Triwahyuni; Kustiyowati (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2026)
Facts on the ground show students' low critical thinking skills. Students' difficulties in understanding the material lead to low levels of critical thinking. This study aims to create a Google Sites learning media to improve students' critical thinking skills. The research design used in this study is developmental, employing the ADDIE model. The main research subjects were 30 sixth-grade students. Data collection methods were carried out both quantitatively and qualitatively, including expert-judgment validation sheets, critical-thinking ability tests (pre-test and post-test), student activity observation sheets, and student response questionnaires. The data analysis used was validity, practicality, and effectiveness analyses. The main results of the study indicate that it is valid, practical, and effective in improving the critical thinking skills of elementary school students, especially in mathematics, making it an alternative, innovative digital media for 21st-century learning. Therefore, developing Google Sites learning media is feasible, practical, and effective for improving students' critical thinking skills. The implications of this study strengthen the theory that integrating web-based digital technology can improve critical thinking skills.